High-Resolution Speckle Imaging at Gemini-North: Exoplanets and Beyond - Howell, Steve B.; Horch, E.; Everett, M. E.; Ciardi, D. (American Astronomical Society, AAS Meeting, 2013)
Using our state-of-the-art 2-channel speckle imaging instrument, we have recently obtained diffraction-limited optical images at the 8-m Gemini-N telescope. The primary science goal was to search for faint (delta_mag = 4-6 mag) and nearby (<0.05") stellar companions around potential planet hosting stars as part of the small small exoplanet validation for the NASA Kepler and ESA CoRoT missions. As a demonstration of the instrument capabilities on Gemini, we achieved an angular resolution of ~20 mas which yielded the highest resolution ground-based optical image of the Pluto-Charon system ever obtained. Our instrument is likely to return to Gemini-N in mid-2013 for observations by general community programs
Keywords: dept.phy

The Relation Between Radius, Mass, and Incident Flux of Exoplanets - Weiss, Lauren M.; Marcy, G. W.; Rowe, J.; Isaacson, H. T.; Howard, A.; Fortney, J. J.; Miller, N.; Demory, B.; Fischer, D.; Adams, E. A.; Dupree, A. K.; Howell, S. B.; et al. (American Astronomical Society, AAS Meeting, 2013)
We measure the mass of a modestly irradiated giant or "warm Jupiter," KOI-94d, in order to calculate its density. We wish to determine whether this planet, which is in a 22 day orbit and receives 107 times as much incident flux as the Earth, is bloated like "hot Jupiters" or as dense as our own Jupiter. In addition to its warm Jupiter, KOI-94 hosts at least 3 smaller planets, all of which were detected through transits by the Kepler Mission. This presents the opportunity to characterize a multi-planet system and to test dynamic stability and formation theory through observations of the masses and orbital elements of these planets. With 26 radial velocity measurements of KOI-94 from the W. M. Keck Observatory/HIRES, we measure the mass of the giant planet and upper limits to the masses of the three smaller planets. Transit timing variations will allow us to hone the mass measurements of the three smaller planets. Using the KOI-94 system and all other planets with published values for both mass and radius, we establish two fundamental planes for exoplanets that relate their mass, incident flux, and radius from a few Earth masses up to ten Jupiter masses: log(Rp/RE) = 0.007 + 0.53 log(M/ME) - 0.001 log(F/[erg/s/cm^2]) for Mp < 150ME; log(Rp/RE) = 0.67 - 0.036 log(M/ME) + 0.06 log(F/[erg/s/cm^2]) for Mp > 150ME. We also solve these planes in density-mass-flux space: log(ρp/[g/cm^3]) = 0.69 - 0.57 log(M/ME) + 0.02 log(F/[erg/s/cm^2]) for Mp < 150ME; log(ρp/[g/cm^3]) = -1.23 + 1.10 log(M/ME) - 0.18 log(F/[erg/s/cm^2]) for Mp > 150ME.
Keywords: dept.phy

Exoplanet Characterization by Proxy for Kepler-61b: How a Nearby Star Bumped a Planet Out of the Habitable Zone - Ballard, Sarah; Charbonneau, D.; Fressin, F.; Torres, G.; Irwin, J.; Desert, J.; Ciardi, D.; Crepp, J. R.; Henze, C.; Bryson, S.; Howell, S. B.; Horch, E.; et al. (American Astronomical Society, AAS Meeting, 2013)
We present the validation and characterization of Kepler-61b: a 2.5 R_Earth planet orbiting near the inner edge of the habitable zone of a low-mass star. Our characterization of the host star Kepler-61 is based upon our identification of a spectroscopically similar star located 4.9 pc from Earth. This proxy star to Kepler-61 has a published direct interferometric radius and effective temperature measurement, which we apply in tandem with the Kepler photometry to characterize the planet Kepler-61b. The technique of identifying a nearby proxy star with directly measured properties allows for an independent check on stellar characterization via the traditional measurements with stellar spectra and evolutionary models. In this case, such a check had profound implications for the putative habitability of Kepler-61b. This work was performed in part under contract with the California Institute of Technology (Caltech) funded by NASA through the Sagan Fellowship Program
Keywords: dept.phy

The Kepler follow-up observation program. I. a catalog of companions to Kepler stars from high-resolution imaging - Furlan, E.; Ciardi, D. R.; Everett, M. E.; Saylors, M.; Teske, J. K.; Horch, E. P.; Howell, S. B.; van Belle, G. T.; Hirsch, L. A.; Gautier, T. N.; Adams, E. R.; Barrado, D.; et al. (The Astronomical Journal, 2017)
We present results from high-resolution, optical to near-IR imaging of host stars of Kepler Objects of Interest (KOIs), identified in the original Kepler field. Part of the data were obtained under the Kepler imaging follow-up observation program over six years (2009-2015). Almost 90% of stars that are hosts to planet candidates or confirmed planets were observed. We combine measurements of companions to KOI host stars from different bands to create a comprehensive catalog of projected separations, position angles, and magnitude differences for all detected companion stars (some of which may not be bound). Our compilation includes 2297 companions around 1903 primary stars. From high-resolution imaging, we find that ∼10% (∼30%) of the observed stars have at least one companion detected within 1″ (4″). The true fraction of systems with close (≲4″) companions is larger than the observed one due to the limited sensitivities of the imaging data. We derive correction factors for planet radii caused by the dilution of the transit depth: assuming that planets orbit the primary stars or the brightest companion stars, the average correction factors are 1.06 and 3.09, respectively. The true effect of transit dilution lies in between these two cases and varies with each system. Applying these factors to planet radii decreases the number of KOI planets with radii smaller than 2 R⊕ by ∼2%-23% and thus affects planet occurrence rates. This effect will also be important for the yield of small planets from future transit missions such as TESS. © 2017. The American Astronomical Society. All rights reserved.
Keywords: binaries: general; catalogs; dept.phy; peer-reviewed; planets and satellites: detection; surveys; techniques: high angular resolution; techniques: photometric

Erratum: “The Kepler Follow-up Observation Program. I. A Catalog of Companions to Kepler Stars from High-resolution Imaging” (2017, AJ, 153, 71) - Furlan, E.; Ciardi, D. R.; Everett, M. E.; Saylors, M.; Teske, J. K.; Horch, E. P.; Howell, S. B.; Belle, G. T. van; Hirsch, L. A.; Gautier, T. N.; Adams, E. R.; Barrado, D.; et al. (The Astronomical Journal, 2017)
We have added references to Tables 3 and 8 (last column in each table). Below is a sample of both tables; the full tables are available in machine-readable form.
Keywords: dept.phy